1995
DOI: 10.1074/jbc.270.9.4457
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Identity and Antigenic Cross-reactivity of White Face Hornet Venom Allergen, Also a Hyaluronidase, with Other Proteins

Abstract: White face hornet (Dolichovespula maculata) venom has three known protein allergens which induce IgE response in susceptible people. They are antigen 5, phospholipase A1, and hyaluronidase, also known as Dol m 5, 1, and 2, respectively. We have cloned Dol m 2, a protein of 331 residues. When expressed in bacteria, a mixture of recombinant Dol m 2 and its fragments was obtained. The fragments were apparently generated by proteolysis of a Met-Met bond at residue 122, as they were not observed for a Dol m 2 mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 34 publications
4
35
0
4
Order By: Relevance
“…Expression of the cloned cDNA in Ercherichio coli yielded a polypeptide with hyase activity. Recently, the amino acid sequence of the enzyme from hornet venom has also been determined via cDNA cloning (Lu et al, 1995). This hyase comprises 331 amino acids, of which 56% are identical to the bee venom hyase.…”
Section: Hyaluronate Lyase (Ec 42991)mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the cloned cDNA in Ercherichio coli yielded a polypeptide with hyase activity. Recently, the amino acid sequence of the enzyme from hornet venom has also been determined via cDNA cloning (Lu et al, 1995). This hyase comprises 331 amino acids, of which 56% are identical to the bee venom hyase.…”
Section: Hyaluronate Lyase (Ec 42991)mentioning
confidence: 99%
“…A comparison of the sequence of bee and hornet venom hyases Lu et al, 1995) with those of human, monkey, mouse, and guinea pig PH-20 protein (Lathrop et al, 1990;Y. Lin et al, 1993Y.…”
Section: Comparative Aspectsmentioning
confidence: 99%
“…The sequence of this enzyme was found to be homologous to PH-20, a polypeptide localized on the head of guinea pig sperm (Lathrop et al, 1990). It could subsequently be demonstrated that PH-20 from different mammalian species has hyaluronidase activity Lin et al, 1994a;Cherr et al, 1996).A comparison of the amino acid sequences of bee and hornet venom hyaluronidases Lu et al, 1995) and those of the human, monkey, mouse, and guinea pig PH-20 proteins (Lathrop et al, 1990; Lin et al, 1994a, b) demonstrated that in a common region encompassing about 340 amino acids, 57 amino acids are conserved in all of these proteins (Fig. 1).…”
mentioning
confidence: 99%
“…A comparison of the amino acid sequences of bee and hornet venom hyaluronidases Lu et al, 1995) and those of the human, monkey, mouse, and guinea pig PH-20 proteins (Lathrop et al, 1990; Lin et al, 1994a, b) demonstrated that in a common region encompassing about 340 amino acids, 57 amino acids are conserved in all of these proteins (Fig. 1).…”
mentioning
confidence: 99%
“…The venom allergens of bees, fire ants and vespids of known sequences and structures are listed in table 2 [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. The vespids include hornets, yellow jackets and paper wasps.…”
Section: Biochemical Studies Of Hymenoptera Venom Allergensmentioning
confidence: 99%